Conjunctivitis in a Juvenile Red-Eared Slider (Trachemys scripta elegans) - Govendan, Puveanthan Nagappan; Purbantoro, Steven Dwi (Faculty of Veterinary Medicine Universitas Brawijaya, 2020)
Conjunctivitis is a common problem among red-eared sliders (Trachemys scripta elegans) with improper husbandry care. A 30 grams T. s. elegans was presented with complaints of anorexia, dullness, inflamed, and closed eyes. The owner informed that the turtle was kept indoors without ultraviolet B (UVB) light or sunlight exposure and the water was not changed by the owner for a week. Clinical examination showed inflammation and watery discharge was found on the left eye. Conjunctivitis was diagnosed based on history and clinical examination. Treatments consist of topical antibiotic drops, vitamin A and B-complex, and husbandry care improvement. The turtle started eating five days after treatment. Ten days after the treatment the turtle was brought back for a checkup and eye have recovered.